Social Media And Body Image Dissatisfaction From The Perspective Of Urban Male Undergraduates - Khoo, Rubin Bu Boen (2020)
Research on body image has largely focused on the female experience although it has been established that men are afflicted by body image dissatisfaction too. This has resulted in a limited understanding of the relationship between body image dissatisfaction and men, particularly when looking at it from a Malaysian context. In recent years, social media has also emerged as an influential medium, particularly among adolescents. The objective of this study is to examine the role of social media in the development of body image dissatisfaction among male adolescents. The study was conducted using male undergraduates from three institutions of higher learning in the Klang Valley using semi-structured interviews and focus groups. The results exhibit that the male experience of body image is a complex one, further accentuated by the way men interact with social media. Participants acknowledged that they engaged in social comparison which often left them feeling insecure. However, they also responded by saying that they see this as a form of motivation for self-improvement. The study has implications in the way body image and men is studied.